Red-emitting CsPbBrI2/PbSe heterojunction nanocrystals with high luminescent efficiency and stability for bright light-emitting diodes. (December 2019) - Zhang, Jibin; Liu, Xiangfu; Jiang, Pengfei; Chen, Hongting; Wang, Yao; Ma, Jinming; Zhang, Rui; Yang, Fei; Wang, Mingkui; Zhang, Jian; Tu, Guoli
Abstract: All inorganic perovskite CsPbX3 (X = Cl, Br, I) nanocrystals (NCs) have been endowed great promise for optoelectronic device applications. However, further practical applications of these NCs are blocked because of their poor stability. In the present work, we propose a novel strategy to synthesize highly luminescent and stable red-emitting CsPbBrI2 /PbSe heterojunction nanocrystals (h-NCs) via an epitaxial solution growth method, in which lattice-matching condition between CsPbBrI2 and PbSe was satisfied, and each CsPbBrI2 NC was partially covered by PbSe in the CsPbBrI2 /PbSe heterodimers. The ultrafast transient absorption (TA) and time-resolved photoluminescence (TRPL) spectroscopy revealed that incorporation of PbSe can modify surface and hence passivate the surface trap states of the CsPbBrI2 NCs, helping to enhance the photoluminescence quantum yields (PLQY) (up to 83.4%) of these CsPbBrI2 /PbSe h-NCs. First-principle calculations based on DFT confirmed that the significantly improved stability of these CsPbBrI2 /PbSe h-NCs was attributed to the strong chemical bonding of selenium atoms of PbSe and lead atoms of PbX2 -terminated surface from CsPbBrI2 . Thin films of these CsPbBrI2 /PbSe h-NCs can maintain bright red PL brightness and cubic phase even after 15-day storage under a high humidity condition. Benefiting from the performances of high stability and luminescent efficiency, these red-emitting CsPbBrI2 /PbSe h-NCs have a positive implication for bright light-emitting diodes (LEDs). Graphical abstract: CsPbBrI2 /PbSe heterojunction nanocrystals (h-NCs) show higher stability and photoluminescence quantum yield (PLQY) than those of pristine CsPbBrI2 NCs. Thin films of these CsPbBrI2 /PbSe h-NCs can maintain bright red PL brightness and cubic phase even after 15-day storage under a high humidity condition, while pristine CsPbBrI2 NCs will decompose and show green PL brightness within exposure to 15 days under the same conditions. Image 1 Highlights: Highly luminescent and stable red-emitting CsPbBrI2 /PbSe heterojunction nanocrystals (h-NCs) were synthesized. PbSe can reduce the trap state density and suppress non-radiative recombination of these CsPbBrI2 /PbSe h-NCs. The stability of CsPbBrI2/PbSe h-NCs origins from the strong bonding between Se atoms of PbSe and Pb atoms of CsPbBrI2 . These CsPbBrI2 /PbSe h-NCs can be used as efficient light emitters for bright light-emitting diodes.